2001
DOI: 10.2166/wst.2001.0214
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic digestion of a nonionic surfactant: inhibition effect and biodegradation

Abstract: Nonionic surfactants are used worldwide in various industrial and household applications. Since these compounds are used in aqueous solutions, they primarily enter the environment through sewage and industrial wastewater treatment plants. The objective of this work was to evaluate the inhibitory effect of Triton X-100, a commercial nonionic surfactant, on the anaerobic digestion of lactose. Thus non-ionic surfactants acts as a non-competitive inhibitor with K1 = 250 mgL-1 and a inhibition order of 2.4. Nonethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Ferguson and Brown well [39] and Jimenez-Gonzalez et al [40], have reported poor anaerobic degradation due to detergents, mainly as a result of process inhibition [41][42]. Even though the kh values from this study are close to the values reported by Mahmoud [34] and Luo et al [15], and the values also fall within the ranges reported by Aldin [16], there is need for caution in comparison of the values due to the different experimental conditions.…”
Section: Discussionsupporting
confidence: 80%
“…Ferguson and Brown well [39] and Jimenez-Gonzalez et al [40], have reported poor anaerobic degradation due to detergents, mainly as a result of process inhibition [41][42]. Even though the kh values from this study are close to the values reported by Mahmoud [34] and Luo et al [15], and the values also fall within the ranges reported by Aldin [16], there is need for caution in comparison of the values due to the different experimental conditions.…”
Section: Discussionsupporting
confidence: 80%
“…The SDS was used below its CMC to minimize surfactant adsorption to GAC. Although Tween 80 was not the most effective non‐ionic surfactant, it is a food‐grade surfactant that may enhance contaminant biodegradation, while being less inhibitory toward some anaerobic cultures than either Brij 30 or Triton X‐100 ( Jiménez‐González et al, 2001 ; Yeh et al, 1998 ). Additionally, Tween 80 can be used at low concentrations because of its low CMC (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory effect of a surfactant on the biodegradation capability may have its origin in any of the following (i) toxicity, (ii) preferential use as substrate, as carbon source alternative to the pollutant, (iii) low pollutant concentration in the aqueous phase by a miscellation effect or (iv) the possibility that the surfactant acts as an interference in the microbial metabolic processes 15. The surfactant Triton X100 has a toxic effect on aerobic microorganism,28 inhibiting the mineralization of glucose29 by anaerobic microorganisms30 acting as non‐competitive inhibitor on the acetogenic and methanogenic acetoclastic activities while affecting neither the fermentative nor the hydrogentrophic activities 31. These effects may be derived from an alteration in the function of the cell cytoplasmatic membrane29 due to the partial lysis that the surfactant Triton X100 exerts on the cell wall 32.…”
Section: Discussionmentioning
confidence: 99%